Girls to the Rescue, Book 1. - Lansky, Bruce (New York : Meadowbrook Press, 1995)
A collection of ten stories featuring admirable girls in both familiar and exotic settings
Fairy godmother's assistant-Grandma Rosa's bowl-For love of Sunny-Carla and the greedy merchant-Savannah's piglets-Kimi meets the ogre-the innkeeper's wise daughter-The royal joust-Chardae's thousnad and one nights-Lian and the unicorn